Royal Commission on Equal Pay 1944-46
1946 1945-1960 "Royal Commission on Equal Pay 1944-46" [EP0078], 1944-1946 In 1946, the Royal Commission on Equal Pay concluded tentatively that women in teaching and certain grades of the civil service might benefit from equal pay. Even these very limited proposals were rejected as inflationary by the Labour Government. Three women [including Anne Loughlin] on the Commission thought equal pay should be extended to women in industry and produced a minority report.